Definitive concurrent chemoradiation versus laryngectomy and postoperative radiation using IMRT in locally advanced laryngeal cancer: experience from a regional cancer centre of Eastern India. Issue 1 (7th March 2021) - Das, Subhadip; Lahiri, Debarshi; Dam, Aniruddha; Maji, Tapas; Roy, Sanjoy; Ray, Dilip Kumar; Mandal, Syamsundar
Abstract: Introduction: For patients with locally advanced laryngeal cancer, two main treatment options are either up-front surgery [total laryngectomy (TL)] followed by postoperative adjuvant radiation therapy (RT) or definitive concurrent chemoradiation (CCRT) with surgery retained as salvage. The objectives were to study the feasibility of CCRT using intensity-modulated radiation therapy (IMRT) in locally advanced laryngeal cancer with respect to response, toxicities, and quality of life (QoL) and comparison with other modality—TL with post-operative RT. Material and Methods: The records of 48 patients with locally advanced laryngeal cancer (T3/T4aN0-2), registered between years 2014 and 2017, treated with IMRT (definitive or adjuvant postoperative IMRT) were analysed from the hospital database. The patients received RT either as definitive CCRT or as adjuvant treatment after TL. RT in all patients was delivered with IMRT-SIB(simultaneous integrated boost) technique and concurrent chemotherapy with weekly cisplatin. The response was assessed at 12 weeks. Toxicities and QoL were assessed and compared between patients receiving definitive CCRT and adjuvant RT. Results: 92·3% patients who received definitive CCRT achieved complete response. Toxicities were of low grade in patients receiving both definitive and adjuvant treatments. All the patients (except two partial responders of CCRT) remained disease-free at the last follow-up. At 2 years of follow-up of each patient—Global QoL, emotional and social functioning were better in definitive CCRT patients. Laryngectomy patients had more dyspnoea, insomnia and financial difficulties. Although the problems of dry mouth, sticky saliva and swallowing were comparable, laryngectomy patients faced more problems with speech, senses, social eating, social contact and cough. Conclusions: Definitive CCRT using IMRT-SIB with weekly cisplatin is a feasible option for patients of locally advanced laryngeal cancer with acceptable response rate. IMRT yields better toxicity outcomes with sparing of organs at risk. CCRT patients have better QoL than laryngectomy patients in several parameters.